The Role of Pharmacological Therapy and Psychotherapy in Post Stroke Depression - Nurlia Puspita Ratnasari (HM Publisher, 2021)
The most prevalent emotional illness following a stroke is post-stroke depression. Some of the symptoms of post-stroke depression include loss of interest, decreased energy, decreased appetite, problems sleeping, self-blame, and even suicide thoughts. To overcome the symptoms of post-stroke depression requires comprehensive management. In the PSD population, antidepressant medication has demonstrated to be effective. In order to obtain comprehensive health services, rehabilitation activities are also required as one of the therapies in the psychological sector of patients with post-stroke depression.